Implementation of B2B E-Commerce in the Enterprise Market - Rizki Qoriah; Edwanda Arisandy; Sausan Hidayah Nova; Hanif Prasetyo bhakti Adi Nugroho; Eko Sediyono; Aris Puji Widodo (Sistemasi: Jurnal Sistem Informasi, 2022)
E-commerce is an online sales system that allows the process of purchasing goods and services via the internet in various business fields, including business-to-business (B2B). B2B or Business-to-Business is an electronic transaction that occurs between one business and another, in which the sale of products provided by a business is intended for another business. This study aims to discuss marketing technology in the corporate market, especially in the B2B section. The method used in this study is a Systematic Literature Review (SLR) on papers regarding the implementation of Enterprise Resource Planning (ERP) planning which has the potential to significantly complement the use of business-to-business e-commerce technology. There are three Research Questions (RQ) set in this study. The results obtained from this study indicate that the potential presence of an ERP system effectively impacts the future economic development-based transaction costs associated with B2B e-commerce technology, while additional planning to ensure that the implementation of B2B e-commerce ERP is supported by incentives related to transaction-based communication costs savings.